Mykhailo Pavlovych Lisitsa (to the 100th anniversary of his birth) - Belyaev, O.Ye.; Blons’kyi, I.V.; Brodyn, M.S.; Vakulenko, O.V.; Valakh, M.Ya.; Kochelap, V.O.; Poperenko, L.V.; Rudko, G.Yu.; Syzov, F.F.; Tarasov, G.G.; Yukhymchuk, V.O. (Ukrainian Journal of Physics, 2021)
-